Enabling always-available input: through on-body interfaces - Saponas, Scott (CHI EA '09 CHI '09 Extended Abstracts on Human Factors in Computing Systems, 2009)
Most current input devices require dedicated attention by our hands through physical transducers such as the keys on a keyboard. Similarly, computer output is dominated by visual displays requiring most of our visual attention. While keyboards and monitors are effective I/O devices for dedicated computing activities, when our primary task is not using a computer, our hands may not be free to manipulate an input device. The goal of my dissertation is to explore how on-body interfaces can better support computing in our everyday activities.